2015
DOI: 10.1080/15456870.2015.1013101
|View full text |Cite
|
Sign up to set email alerts
|

Media Use and Health Behavior in H1N1 Flu Crisis: The Mediating Role of Perceived Knowledge and Fear

Abstract: First detected in 2009, H1N1 flu has caused human causalities and become one of the top global health concerns. This study examined the relationship between the use of mass media for information about H1N1 flu and health-related behaviors. Past studies have focused primarily on the direct effects of media exposure on engagement in preventative behaviors. This study took a step forward by investigating the underlying mechanism in this relationship. Data from a web-based survey of college students showed that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 31 publications
4
84
1
1
Order By: Relevance
“…Ho (2012), for example, found that attention to newspaper and television news increased public knowledge about the H1N1 pandemic. Zhang et al (2015) also found that media use potentially influenced H1N1 preventive behaviors through fear and perceived knowledge. The results of 36 national surveys in the United Kingdom indicate that exposure to media coverage or advertising about swine flu increased the adoption of recommended preventive behaviors (G. Rubin, Potts, & Michie, 2010).…”
Section: Cognitive and Behavioral Responsesmentioning
confidence: 92%
“…Ho (2012), for example, found that attention to newspaper and television news increased public knowledge about the H1N1 pandemic. Zhang et al (2015) also found that media use potentially influenced H1N1 preventive behaviors through fear and perceived knowledge. The results of 36 national surveys in the United Kingdom indicate that exposure to media coverage or advertising about swine flu increased the adoption of recommended preventive behaviors (G. Rubin, Potts, & Michie, 2010).…”
Section: Cognitive and Behavioral Responsesmentioning
confidence: 92%
“…Media use has a profound impact on knowledge acquisition at a time of crisis [ 37 ], especially when the entire society is virtually locked down. Meanwhile, media reports can also fuel fear [ 38 ]. Modern information technology has broadened the source of information dramatically.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding how individuals experience and respond to an infectious disease outbreak can be derived from the extended parallel process model (EPPM) (Witte, 1992(Witte, , 1994. The EPPM has been widely employed in predicting preventive behaviors during infectious disease outbreaks (e.g., Balicer et al, 2010;Siu, 2008;Zhang, Kong, & Chang. 2015).…”
Section: Cognitive Mechanisms: Mediating Roles Of Self-efficacy and Pmentioning
confidence: 99%